Protective Effects of 6-Gingerol on Cardiotoxicity Induced by Arsenic Trioxide Through AMPK/SIRT1/PGC-1α Signaling Pathway - Han, Xue; Yang, Yakun; Zhang, Muqing; Chu, Xi; Zheng, Bin; Liu, Chenxu; Xue, Yucong; Guan, Shengjiang; Sun, Shijiang; Jia, Qingzhong (Frontiers in Pharmacology, 2022)
Background and Objective: Arsenic trioxide (As2O3) induced cardiotoxicity to limit the clinical applications of the effective anticancer agent. 6-Gingerol (6G) is the main active ingredient of ginger, a food with many health benefits. The present study aims to investigate the potential pharmacological mechanisms of 6G on As2O3-induced myocardial injury. Methods and Results: Fifty KunMing mice were divided into 5 groups (n = 10) receiving: 1) physiological saline; 2) 6G (20 mg/kg) alone; 3) As2O3 (5 mg/kg); 4) 6G (10 mg/kg) and As2O3 (5 mg/kg); 5) 6G (20 mg/kg) and As2O3 (5 mg/kg). 6G was given orally and As2O3 was given intraperitoneally once per day for 7 consecutive days. Biochemical, histopathological, transmission electron microscopy, ELISA, and western blotting analyses were then performed. Based on the resultant data, As2O3 was found to induce cardiotoxicity in mice. 6G significantly ameliorated As2O3-induced heart injury, histopathological changes, oxidative stress, myocardial mitochondrial damage, inflammation, and cardiomyocyte apoptosis, while reversed As2O3-induced inhibition of the AMPK/SIRT1/PGC-1α pathway. Conclusion: Our experimental results reveal that 6G effectively counteracts As2O3-induced cardiotoxicity including oxidative stress, inflammation and apoptosis, which might be attributed to its activation action on AMPK/SIRT1/PGC-1α signaling pathway.